2018
DOI: 10.3389/fnana.2018.00037
|View full text |Cite
|
Sign up to set email alerts
|

MultiMap: A Tool to Automatically Extract and Analyse Spatial Microscopic Data From Large Stacks of Confocal Microscopy Images

Abstract: The development of 3D visualization and reconstruction methods to analyse microscopic structures at different levels of resolutions is of great importance to define brain microorganization and connectivity. MultiMap is a new tool that allows the visualization, 3D segmentation and quantification of fluorescent structures selectively in the neuropil from large stacks of confocal microscopy images. The major contribution of this tool is the posibility to easily navigate and create regions of interest of any shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…• MultiMap (Figure 3J), an extensible application to deal with large stacks of confocal microscopic images at different levels of resolutions (Varando et al, 2018). The possibility of creating regions of interest (of any shape and size) is a great advantage of the tool.…”
Section: Neuro Apps Without Neurons Requiredmentioning
confidence: 99%
“…• MultiMap (Figure 3J), an extensible application to deal with large stacks of confocal microscopic images at different levels of resolutions (Varando et al, 2018). The possibility of creating regions of interest (of any shape and size) is a great advantage of the tool.…”
Section: Neuro Apps Without Neurons Requiredmentioning
confidence: 99%
“…A recent study using a Gaussian filter and an automated object detection process reported a new approach to a fast and accurate 3D analysis of fluorescent puncta in the neuropil of large brain areas, avoiding the more tedious deconvolution procedure (Varando et al, 2018). In our study, we used the deconvolution procedure for the analysis of 2D confocal images, which gives also an accurate bouton quantification to define the inhibitory profile of the ferret visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Although image analysis exists for these applications, they are much less advanced compared with WSI. [9][10][11]…”
Section: Technologies For Tissue Biomarker Detection Histochemistry I...mentioning
confidence: 99%
“…For example, microscopy with UV surface excitation imaging relies on illuminating unstained tissues with UV light at wavelengths <300 nm, which allows visualization of cellular properties in tissues with similar information content to H&E stains, but without the need for fixation and processing. Although image analysis exists for these applications, they are much less advanced compared with WSI 9–11…”
Section: Technologies For Tissue Biomarker Detectionmentioning
confidence: 99%